High-strength wall fireproof thermal insulation material and preparation method thereof
By hydrophobic modification of expanded perlite and mixing with Si-Al aerogel and other materials, the problem of increasing thermal conductivity caused by its water absorption is solved, the hydrophobicity and flame retardant properties of the material are improved, and high strength and good Preparation of wall fire-proof insulation materials with thermal insulation and fire-proof effects.
Patent Information
- Application Number
- CN202411226140.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The super-strong water-absorbing properties of expanded perlite lead to a significant increase in its thermal conductivity, reducing the thermal insulation ability and limiting its application; at the same time, the improper Silicate Inorganic Materials content leads to low preparation efficiency and gel The problem of poor intensity.
The expanded perlite was hydrophobicly modified and mixed with Si-Al aerogel, UPF foaming material, carbon nanotubes and composite foaming agent. The Si-Al complex was prepared by metakaolin, using Al salt and B orthosilicate. Ester regulator, adjusts the silicon-aluminum ratio, combines epoxy resin, and forms Si-Al aerogel after freeze-drying, enhances the strength of the skeleton, and mixes it with modified perlite, carbon nanotubes and composite foaming agent to prepare high strength by casting. Wall fireproof insulation material.
The hydrophobicity and surface roughness of expanded perlite are improved, the bonding force with the matrix is enhanced, the dispersion effect and flame retardant performance of the material are significantly improved, the thermal conductivity is reduced, and the thermal insulation and flame retardant performance is enhanced.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of thermal insulation material preparation, in particular to a high-strength wall fireproof thermal insulation material and a preparation method thereof. Background Art
[0002] Expanded perlite is an acidic volcanic glass mineral that is widely found in volcanic rocks. It is an internally porous pearl-structured material formed during the rapid cooling of high-temperature magma erupted after a volcanic eruption. It has a loose, porous internal structure, as well as low density, low thermal conductivity, strong adsorption and other characteristics. It has a wide source and abundant reserves on the earth, and has great application potential in inorganic thermal insulation materials.
[0003] However, the honeycomb pore structure of expanded perlite makes it have super water absorption performance. When a large amount of water is absorbed by the expanded perlite, the voids inside its pores are replaced by water molecules, which is equivalent to adding many thermal bridges inside. The thermal conductivity of the expanded perlite after absorbing water or water vapor will be several times that of the dry expanded perlite. The thermal insulation capacity of the expanded perlite products is greatly reduced, which also limits the promotion and application of expanded perlite.
[0004] Some silicate inorganic substances are rich in SiO2 and Al2O3 materials, which can be used to prepare polymer gels in solution systems. The aerogels prepared in this way also have good cross-linking strength and thermal insulation properties. However, the Si content and Al content therein are different from those required to form a gel, resulting in slow preparation efficiency, the presence of silicon and aluminum oligomers, and low gel strength. Summary of the invention
[0005] The object of the present invention is to provide a high-strength wall fireproof and thermal insulation material and a preparation method thereof to solve the problems raised in the background technology. After the expanded perlite is hydrophobically modified, it is mixed with Si-Al aerogel, UPF foaming material, carbon nanotubes and composite foaming agent to prepare the high-strength wall fireproof and thermal insulation material. The perlite is modified to increase the hydrophobicity and surface roughness of the perlite, provide more contact area for it in the thermal insulation material system, and improve its bonding force with the matrix, thereby showing a better dispersion effect. The Si-Al composite is prepared using metakaolin, and the silicon-aluminum regulator is prepared using Al salt and tetraethyl orthosilicate respectively, the silicon-aluminum ratio in the composite is adjusted, and then mixed with epoxy resin, and Si-Al aerogel is obtained after freeze drying. The protons generated by the reaction are used as nucleophilic reagents to open the epoxy groups on the epoxy resin, which can consume the protons generated by the reaction, promote the crosslinking of the gel, and enhance the skeleton strength of the obtained aerogel after curing. The prepared material has the characteristics of good flame retardant effect, thermal insulation, and pourable preparation.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a high-strength wall fireproof and thermal insulation material comprises the following steps:
[0008] S1. Collect expanded perlite material, perform hydrophobic modification on it, and obtain modified perlite. The specific operation is as follows:
[0009] (A1) adding 1-5 mL of 20-30% acid solution to 100 mL of 30%-50% mass concentration hydrogen peroxide solution to obtain an oxidant solution; washing the expanded perlite with deionized water, draining the water and naturally drying it, then adding it to the oxidant solution at a bath ratio of 1 g: 20 mL, stirring evenly, raising the system temperature to 50-80° C., treating for 30-90 minutes, and obtaining oxidized perlite;
[0010] (A2) adding 0.585 g of 0.1 mol / L 2-morpholineethanesulfonic acid and 0.0876 g of 0.05 mol / L NaCl to 30 mL of oxidized perlite system, adjusting the pH value of the system to 5.1, to obtain 2-morpholineethanesulfonic acid buffer for later use;
[0011] (A3) 0.192 g of EDC, 0.115 g of N-hydroxysuccinimide and (0.1-1.0) g of dopamine hydrochloride are dissolved in the 2-morpholineethanesulfonic acid buffer prepared in step A2, and the mixture is stirred for 24 hours at room temperature under an inert gas atmosphere. Subsequently, a 1-6% sodium methyl silicate solution is added, and the mixture is soaked for 60 minutes, filtered, and washed with deionized water until the pH value of the washing solution is neutral, thereby obtaining modified perlite.
[0012] During the above reaction process, the surface of expanded perlite contains more hydroxyl and carboxyl groups. Hydrogen peroxide and weak acid solution are used to oxidize the hydroxyl groups on the surface of expanded perlite into carboxyl groups. Then, dopamine hydrochloride is used to modify the oxidized expanded perlite. The amino groups on dopamine are combined with the carboxyl groups obtained by oxidation to form amide bonds, thereby grafting on the surface of expanded perlite. Under the action of oxidizing hydrogen peroxide in the system, the catechol groups are oxidized to generate quinones. Due to the hydrophobic properties of the benzene ring, the hydrophobic properties of the expanded perlite are increased. Subsequently, in the weak acid environment of the buffer solution, sodium methyl silicate is decomposed into methyl silicic acid by weak acid, and a layer of polysiloxane film is formed on the surface of the expanded perlite, so that the expanded perlite has good hydrophobic properties.
[0013] S2, using metakaolin to prepare Si-Al composite, and using Al salt and tetraethyl orthosilicate to prepare silicon-aluminum regulators respectively, adjusting the silicon-aluminum ratio in the composite to prepare a silicon-aluminum prepolymer; then adding epoxy resin to the silicon-aluminum prepolymer, stirring the system evenly, and freeze-drying to obtain Si-Al aerogel, the specific operation is as follows:
[0014] (B1) mixing aluminum chloride hexahydrate: ethanol: water in a molar ratio of 1:16:4, stirring evenly, raising the system temperature to 50°C, and stirring the system at a rate of 30 rpm for 2 hours to obtain an aluminum regulator; mixing tetraethyl orthosilicate: water: ethanol: nitric acid in a molar ratio of 1:4:12:0.001, stirring evenly, raising the system temperature to 50°C, and stirring the system at a rate of 30 rpm for 2 hours to obtain a silicon regulator;
[0015] (B2) adding the metakaolin raw material to the alkaline catalyst and mixing and stirring at a stirring rate of 800 rpm for 3 minutes, then adding the silicon regulator and the aluminum regulator prepared in step B1 to the system and stirring at a rate of 1000 rpm for 3 minutes to obtain a silicon-aluminum prepolymer;
[0016] (B3) Epoxy resin was then added, and after stirring at 300 rpm for 10 min at room temperature, the system was transferred to a pure ethanol solution and aged for 48 h, followed by freeze drying to obtain Si-Al aerogel.
[0017] In the above reaction process, kaolin as aluminosilicate is dissolved in an alkaline environment to produce water-soluble AlO4 and SiO4 monomers. The two monomers undergo condensation reaction to gradually form polymers. The condensation main chain in the polymer is arranged according to Si-O-Si-O-Al-O-Al. By preparing Al regulator and silicon regulator, the molar ratio of SiO2 and Al2O3 in the system is 2:1, and a relatively stable Si-Al gel system can be obtained. Aluminum chloride hexahydrate is selected as the Al regulator. It is soluble in water and exists in the solution in the form of ions to form a complex with water. The OH groups in the system react with each other to remove water molecules, and the oxygen atoms form a network polymer in the form of oxygen bridges, but hydrolysis produces more Cl - It can act as a nucleophilic agent to open the epoxy group on the epoxy resin, which can consume the protons produced by the reaction and promote the cross-linking of the gel. After curing, it can enhance the skeleton strength of the obtained aerogel.
[0018] S3. Mix Si-Al aerogel and UPF foaming material, stir evenly, add modified perlite, carbon nanotubes and composite foaming agent, stir at a rate of 1000 rpm for 3 minutes, then pour and solidify to obtain a high-strength wall fireproof and thermal insulation material.
[0019] Furthermore, in step B2, according to the contents of SiO2 and Al2O3 in the high-temperature territorial water, silicon prepolymer and aluminum prepolymer are used to adjust the molar ratio of Al and Si in the system to 2:1.
[0020] Furthermore, in step B2, the alkaline catalyst is obtained by mixing sodium silicate and sodium hydroxide in a mass ratio of 95:(10-12.3-15).
[0021] Furthermore, the composite foaming agent is obtained by mixing sodium bicarbonate, sodium dodecyl sulfate and phosphoric acid in a mass ratio of 0.08:(0.06-0.1):(0.12-0.14).
[0022] Furthermore, in step S3, the mass ratio of Si-Al aerogel, UPF foaming material, modified perlite, carbon nanotubes and composite foaming agent is (0.01-0.1):1:(0.01-0.1):(0.01-0.05):(0.26-0.32).
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] In the technical solution of the present invention, the expanded perlite is hydrophobically modified and then mixed with Si-Al aerogel, UPF foaming material, carbon nanotubes, composite foaming agent and other materials to prepare high-strength wall fireproof insulation materials. The surface of the expanded perlite contains a large number of hydroxyl and carboxyl groups. Hydrogen peroxide and weak acid solution are used to oxidize the hydroxyl groups on the surface of the expanded perlite into carboxyl groups. Then, dopamine hydrochloride is used to modify the oxidized expanded perlite. The amino groups on the dopamine are combined with the carboxyl groups obtained by oxidation to form amide bonds, thereby grafting on the surface of the expanded perlite. Under the action of oxidizing hydrogen peroxide in the system, the catechol group is oxidized to generate quinones. Due to the hydrophobic properties of the benzene ring, the hydrophobic properties of the expanded perlite are increased. Subsequently, in the weak acid environment of the buffer solution, sodium methyl silicate is decomposed into methyl silicic acid by weak acid, and a layer of polysiloxane film is formed on the surface of the expanded perlite, so that the expanded perlite has good hydrophobic properties. Expanded perlite itself is non-flammable. After being modified with catechol, the expanded perlite can inhibit the free radicals generated by combustion during the combustion process, and can undergo thermal decomposition at high temperatures to generate a carbonized layer. The carbonized layer is a non-flammable substance that can block oxygen and prevent the spread of combustion, and has a better flame retardant effect. In addition, the catechol group grafted on the surface of the expanded perlite can reduce the corrosion of the perlite surface caused by acidic substances, increase the surface roughness of the perlite, provide it with more contact area in the thermal insulation material system, and improve its bonding strength with the matrix, thereby showing a better dispersion effect.
[0025] The Si-Al composite was prepared using metakaolin, and Al salt and tetraethyl orthosilicate were used to prepare silicon-aluminum regulators, respectively, to adjust the silicon-aluminum ratio in the composite, and then mixed with epoxy resin, and freeze-dried to obtain Si-Al aerogel. As a silicate, metakaolin is dissolved in an alkaline environment to produce water-soluble AlO4 and SiO4 monomers. The two monomers undergo condensation reactions to gradually form polymers. The condensation main chain in the polymer is arranged according to Si-O-Si-O-Al-O-Al. By preparing Al regulators and silicon regulators, the molar ratio of SiO2 and Al2O3 in the system is 2:1, and a relatively stable Si-Al gel system can be obtained. Aluminum chloride hexahydrate is selected as the Al regulator, which is soluble in water and exists in the solution in the form of ions to form a complex with water. The OH groups in the system react with each other to remove water molecules, and oxygen atoms form a network polymer in the form of oxygen bridges, but hydrolysis produces more Cl - It can be used as a nucleophilic reagent to open the epoxy group on the epoxy resin, which can consume the protons produced by the reaction and promote the cross-linking of the gel. After curing, it can enhance the skeleton strength of the obtained aerogel. The prepared material has the characteristics of good flame retardant effect, heat preservation, and can be cast. DETAILED DESCRIPTION
[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] The reagents used in the following examples and comparative examples are all of analytical grade. The compositions of the perlite and metakaolin used are shown in Table 1 below.
[0028] Table 1 Composition of perlite and metakaolin
[0029] Group <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[K2O]]> CaO MgO Perlite 70.3 14.6 3.5 0.14 0.39 Metakaolin 55.0 43.9 0.14 0.08 0.02
[0030] Example 1
[0031] The modified perlite is prepared by the following steps:
[0032] (A1) 1 mL of a 20 wt % sulfuric acid solution is added to 100 mL of a 30 wt % hydrogen peroxide solution to obtain an oxidant solution; the expanded perlite is washed with deionized water, the water is drained and the solution is naturally dried in the sun, and then the expanded perlite is added to the oxidant solution at a bath ratio of 1 g: 20 mL, the solution is stirred evenly, the system temperature is raised to 50° C., and the solution is treated for 30 minutes to obtain oxidized perlite;
[0033] (A2) adding 0.585 g of 0.1 mol / L 2-morpholineethanesulfonic acid and 0.0876 g of 0.05 mol / L NaCl to 30 mL of oxidized perlite system, adjusting the pH value of the system to 5.1, to obtain 2-morpholineethanesulfonic acid buffer for later use;
[0034] (A3) 0.192 g of EDC, 0.115 g of N-hydroxysuccinimide and 0.1 g of dopamine hydrochloride were dissolved in the 2-morpholineethanesulfonic acid buffer prepared in step A2, and the mixture was stirred for 24 hours at room temperature under an inert gas atmosphere. Then, a 1 wt % sodium methyl silicate solution was added, and the mixture was immersed for 60 minutes, filtered, and washed with deionized water until the pH value of the washing solution was neutral, thereby obtaining modified perlite.
[0035] Example 2
[0036] The difference between this embodiment and embodiment 1 is that in step A1, the oxidant solution is obtained by adding 3 mL of 25 wt% sulfuric acid solution to 100 mL of 40 wt% hydrogen peroxide solution; the heat treatment condition for preparing oxidized pearlite is 70° C. for 60 minutes. In step A3, the amount of dopamine hydrochloride used is 0.5 g; and the concentration of the sodium methyl silicate solution is 3 wt%.
[0037] Example 3
[0038] The difference between this embodiment and embodiment 1 is that in step A1, the oxidant solution is obtained by adding 5 mL of 30 wt% sulfuric acid solution to 100 mL of 50 wt% hydrogen peroxide solution; the heat treatment condition for preparing oxidized pearlite is 80° C. for 90 minutes. In step A3, the amount of dopamine hydrochloride used is 1.0 g; and the concentration of the sodium methyl silicate solution is 6 wt%.
[0039] Example 4
[0040] Si-Al aerogel is prepared by the following steps:
[0041] (B1) mixing aluminum chloride hexahydrate: ethanol: water in a molar ratio of 1:16:4, stirring evenly, raising the system temperature to 50°C, and stirring the system at a rate of 30 rpm for 2 hours to obtain an aluminum regulator; mixing tetraethyl orthosilicate: water: ethanol: nitric acid in a molar ratio of 1:4:12:0.001, stirring evenly, raising the system temperature to 50°C, and stirring the system at a rate of 30 rpm for 2 hours to obtain a silicon regulator;
[0042] (B2) Sodium silicate and sodium hydroxide are mixed in a mass ratio of 95:10 to obtain an alkaline catalyst; then 100 g of metakaolin raw material is added to 50 g of the alkaline catalyst and mixed and stirred at a stirring rate of 800 rpm for 3 minutes, and then 5.4 g of the silicon regulator prepared in step B1 and 7.14 g of the aluminum regulator are added to the system and stirred at a rate of 1000 rpm for 3 minutes to obtain a silicon-aluminum prepolymer;
[0043] (B3) Then, 5 g of phenolic epoxy resin F51 was added, and after stirring at 300 rpm for 10 min at room temperature, the system was transferred to a pure ethanol solution and aged for 48 h, and then freeze-dried to obtain Si-Al aerogel.
[0044] Example 5
[0045] The difference between this embodiment and embodiment 4 is that in step B2, the base catalyst is obtained by mixing sodium silicate and sodium hydroxide in a mass ratio of 95:12.3. In step B3, the amount of epoxy resin used is 8 g.
[0046] Example 6
[0047] The difference between this embodiment and embodiment 4 is that in step B2, the base catalyst is obtained by mixing sodium silicate and sodium hydroxide in a mass ratio of 95:15. In step B3, the amount of epoxy resin used is 10 g.
[0048] Example 7
[0049] A high-strength wall fireproof and thermal insulation material is prepared by the following steps:
[0050] S1, sodium bicarbonate, sodium dodecyl sulfate, and phosphoric acid are mixed in a mass ratio of 0.08:0.06:0.12, and stirred evenly to obtain a composite foaming agent;
[0051] S2. By mass, 0.01 parts of the Si-Al aerogel prepared in Example 4 was mixed with 1 part of the UPF foaming material, and after stirring evenly, 0.01 parts of the modified perlite prepared in Example 1, 0.01 parts of carbon nanotubes and 0.26 parts of the composite foaming agent were added, and stirred at a rate of 1000 rpm for 3 minutes, followed by pouring and curing to obtain a high-strength wall fireproof and thermal insulation material.
[0052] Example 8
[0053] The difference between this embodiment and embodiment 7 is that in step S1, the composite foaming agent is obtained by mixing sodium bicarbonate, sodium dodecyl sulfate, and phosphoric acid in a mass ratio of 0.08:0.08:0.13. In step S2, Si-Al aerogel is prepared in embodiment 5, and modified perlite is prepared in embodiment 2; the mass ratio of Si-Al aerogel, UPF foaming material, modified perlite, carbon nanotubes and composite foaming agent is 0.05:1:0.03:0.02:0.29.
[0054] Example 9
[0055] The difference between this embodiment and embodiment 7 is that in step S1, the composite foaming agent is obtained by mixing sodium bicarbonate, sodium dodecyl sulfate, and phosphoric acid in a mass ratio of 0.08:0.1:0.14. In step S2, Si-Al aerogel is prepared in embodiment 6, and modified perlite is prepared in embodiment 3; the mass ratio of Si-Al aerogel, UPF foaming material, modified perlite, carbon nanotubes and composite foaming agent is 0.1:1:0.1:0.05:0.32.
[0056] Comparative Example 1
[0057] The difference between this comparative example and Example 8 is that the expanded perlite is not modified in this example.
[0058] Comparative Example 2
[0059] The difference between this comparative example and Example 8 is that in the modification process of the expanded perlite in this example, no sodium methyl silicate solution is added.
[0060] Comparative Example 3
[0061] The difference between this comparative example and Example 8 is that in the process of preparing Si-Al aerogel in this example, no silicon or aluminum regulator is used.
[0062] Comparative Example 4
[0063] The difference between this comparative example and Example 8 is that in this example, epoxy resin is not added to the Si-Al aerogel.
[0064] The thermal insulation and fireproofing effects of the thermal insulation materials prepared in Examples 7-9 and Comparative Examples 1-4 are now tested. The samples are made into square strips with a length of 10 cm and a width of 2 cm. The thermal conductivity of the material is tested using a thermal conductivity tester. Each sample is tested 5 times, and the average value is recorded to determine the thermal insulation effect of the material. 15 strips of each sample are taken. Under the conditions of an ambient temperature of 10-35°C, a relative humidity of 45%-75%, and an air oxygen concentration of 16%-27%, the sample is ignited from the top. After confirming that the top of the sample is completely on fire, the igniter is immediately removed and the burning time is recorded to determine the fireproofing effect of the material. When igniting the sample, the longest time for the flame to act is 30 seconds. If it cannot be ignited within 30 seconds, the oxygen concentration is increased and the ignition is continued until it is ignited within 30 seconds. Each sample is tested 15 times, and the average value is taken. The test results are shown in Table 2 below.
[0065] Table 2 Thermal insulation and fireproofing effect test of thermal insulation materials prepared in Examples 7-9 and Comparative Examples 1-4
[0066] project Thermal conductivity (W / m / K) Burning time(s) Example 7 0.030 0.7 Example 8 0.025 0.4 Example 9 0.028 0.6 Comparative Example 1 0.040 0.9 Comparative Example 2 0.036 0.6 Comparative Example 3 0.037 0.8 Comparative Example 4 0.029 0.9
[0067] As can be seen from Table 2 above, the thermal insulation material prepared in Example 8 has the lowest thermal conductivity and the shortest burning time, and has the best thermal insulation and flame retardant effects. As can be seen from the data in Comparative Examples 1 and 2, the modification of expanded perlite can greatly reduce the water absorption during the preparation process, resulting in the pores being filled with water molecules, which increases the thermal insulation capacity of many thermal bridges. As can be seen from the results in Comparative Example 3, the use of silicon and aluminum regulators to adjust the prepared gel can make the thermal insulation and flame retardant effects of the prepared aerogel structure better. As can be seen from the results in Comparative Example 4, the use of epoxy resin can increase the flame retardancy of the material.
[0068] Now the strength of the thermal insulation materials prepared in Examples 7-9 and Comparative Examples 1-4 is tested, and the compressive strength of the materials is tested respectively. According to GB / T 6342-1996, the maximum compressive force when the relative deformation ε is less than 10% is divided by the initial cross-sectional area of the test piece; the compressive strength is the maximum compressive stress that the material withstands during the compression failure process. Each sample is tested 5 times, and the average value is recorded. The test results are shown in Table 3.
[0069] Table 3 Test of the strength of the thermal insulation materials prepared in Examples 7-9 and Comparative Examples 1-4
[0070] project Compressive strength(MPa) Example 7 0.32 Example 8 0.32 Example 9 0.31 Comparative Example 1 0.23 Comparative Example 2 0.30 Comparative Example 3 0.25 Comparative Example 4 0.26
[0071] From the results in Table 3, it can be seen that the thermal insulation materials prepared in Examples 7-9 all have good compressive resistance. From the results in Comparative Examples 1 and 3, it can be seen that the modification of expanded perlite and the use of silicon and aluminum regulators can improve the mechanical properties of the material including compressive strength. From the results in Comparative Example 4, it can be seen that the use of epoxy resin can improve the strength of the material.
[0072] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0073] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
[0074] project Bacillus inhibition rate (%) Escherichia coli inhibition rate (%) Example 7 99.1 99.6 Example 8 99.8 99.9 Example 9 99.5 99.8 Comparative Example 1 45.6 51.3 Comparative Example 2 69.8 71.3 Comparative Example 3 51.0 53.8
Claims
1. A method for preparing a high-strength wall fireproof and thermal insulation material, characterized in that: The following steps are involved: S1, collecting expanded perlite material, and performing hydrophobic modification on it to obtain modified perlite; S2, using kaolin to prepare Si-Al composite, and using Al salt and tetraethyl orthosilicate to prepare silicon-aluminum regulators respectively, adjusting the silicon-aluminum ratio in the composite to prepare a silicon-aluminum prepolymer; then adding epoxy resin to the silicon-aluminum prepolymer, stirring the system evenly, and freeze-drying to obtain Si-Al aerogel; S3. Mix Si-Al aerogel and UPF foaming material, stir evenly, add modified perlite, carbon nanotubes and composite foaming agent, stir, pour and solidify to obtain a high-strength wall fireproof and thermal insulation material.
2. The method for preparing a high-strength wall fireproof and thermal insulation material according to claim 1, characterized in that: In step S1, the modified perlite is specifically prepared by the following steps: A1. Add the acid solution to the hydrogen peroxide solution to obtain an oxidant solution; wash the expanded perlite with deionized water, drain the water and dry it naturally in the sun, then add it to the oxidant solution at a bath ratio of 1g:20mL, stir evenly and raise the system temperature to 50-80°C. After treating for 30-90 minutes, obtain oxidized perlite; A2, adding 2-morpholineethanesulfonic acid and NaCl to the oxidized perlite system, adjusting the pH value of the system to 5.1, and obtaining a 2-morpholineethanesulfonic acid buffer for standby use; A3. Dissolve 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, N-hydroxysuccinimide and dopamine hydrochloride in the 2-morpholineethanesulfonic acid buffer prepared in step A2, stir well for 24 hours at room temperature under an inert gas atmosphere, then add a sodium methyl silicate solution, soak, filter, and wash the filtrate until the pH value of the washing solution is neutral, thereby obtaining modified perlite.
3. The method for preparing a high-strength wall fireproof and heat-insulating material according to claim 2, characterized in that: In step A3, the mass ratio of dopamine hydrochloride to 2-morpholineethanesulfonic acid buffer is (0.1-1) g:30 mL.
4. The method for preparing a high-strength wall fireproof and heat-insulating material according to claim 1, characterized in that: In step S2, the Si-Al aerogel is specifically prepared by the following steps: B1. Aluminum chloride hexahydrate, ethanol and water were mixed, stirred evenly, and then the system temperature was increased to 50° C., and stirred for 2 hours to obtain an aluminum regulator; ethyl orthosilicate, water, ethanol and nitric acid were mixed, stirred evenly, and then the system temperature was increased to 50° C., and stirred for 2 hours to obtain a silicon regulator; B2, adding the metakaolin raw material to the alkali catalyst and mixing and stirring at a stirring rate of 800 rpm for 3 minutes, then adding the silicon regulator and aluminum regulator prepared in step B1 to the system and stirring at a rate of 1000 rpm for 3 minutes to obtain a silicon-aluminum prepolymer; B3. Then, epoxy resin was added, and after stirring at 300 rpm for 10 minutes at room temperature, the system was transferred to a pure ethanol solution and aged for 48 hours, and then freeze-dried to obtain Si-Al aerogel.
5. The method for preparing a high-strength wall fireproof and heat-insulating material according to claim 4, characterized in that: In step B2, according to the content of SiO2 and Al2O3 in the high-temperature sintered area, silicon prepolymer and aluminum prepolymer are used to adjust the molar ratio of Al and Si in the system to 2:
1.
6. The method for preparing a high-strength wall fireproof and heat-insulating material according to claim 4, characterized in that: In step B2, the catalyst is obtained by mixing sodium silicate and sodium hydroxide in a mass ratio of 95:(10-12.3-15).
7. The method for preparing a high-strength wall fireproof and heat-insulating material according to claim 1, characterized in that: The composite foaming agent is composed of sodium bicarbonate, sodium lauryl sulfate and phosphoric acid at 0.08: The mixture is obtained by mixing in a mass ratio of (0.06-0.1):(0.12-0.14).
8. The method for preparing a high-strength wall fireproof and heat-insulating material according to claim 1, characterized in that: In step S3, the mass ratio of Si-Al aerogel, UPF foaming material, modified perlite, carbon nanotubes and composite foaming agent is (0.01-0.1): 1: (0.01-0.1): (0.01-0.05): (0.26-0.32)。 9. A high-strength wall fireproof and thermal insulation material, characterized in that: Prepared by the preparation method described in any one of claims 1 to 8.
